Response of the inner ear to lipopolysaccharide introduced directly into scala media - Brown, Daniel; Sokolic, L.; Fung, A.; Pastras, C. (2018)
In an attempt to develop an animal model of immune mediated Meniere's disease, we have injected lipopolysaccharide (LPS) directly into scala media of guinea pigs and monitored functional and morphological changes over a period of 6 weeks. Depending on the concentration of LPS, changes ranged from moderate-to-severe hearing loss and endolymphatic hydrops with minimal cellular infiltrate or fibrosis, to dense cellular infiltration that filled the scalae. Interestingly, higher concentrations of LPS not only induced severe cellular infiltration, hydrops, and hearing loss, but also a substantial enlargement of the endolymphatic duct and sac. Moreover, LPS injections into perilymph failed to induce hydrops, yet still resulted in cellular infiltration and fibrosis in the cochlea. This suggests that chronic hydrops resulting from an immune challenge of the cochlea may not be due to blockage of the endolymphatic duct and sac, restricting fluid absorption. Furthermore, injecting antigen into endolymph may produce chronic immune-mediated hydrops, and provide a more promising animal model of Meniere's, although animals did not display signs of vestibular dysfunction, and the hearing loss was relatively severe.